Clinical effect of Changweishu on gastrointestinal dysfunction in patients with sepsis. Issue 8 (August 2020) - Chen, Fen-Qiao; Xu, Wen-Zhong; Gao, Hai-Yun; Wu, Li-Juan; Zhang, He; Cheng, Li; Mei, Jian-Qiang
Objective: To investigate Changweishu's clinical effect on gastrointestinal dysfunction in patients with sepsis. Methods: Fifty patients with gastrointestinal dysfunction and sepsis were randomly divided into treatment and control groups. The control group patients received routine Western medicine treatments (meropenem, noradrenaline, glutamine glue, Bifidobacterium lactis triple-strain tablet), and the treatment group patients received routine Western medicine treatment combined with Changweishu. Treatments in both groups lasted 7 days. Changes in APACHE II score, gastrointestinal dysfunction score, serum levels of diamine oxidase (DAO), D-lactic acid, inflammatory factors (tumor necrosis factor (TNF)-α, interleukin (IL)-6, and high-mobility group box 1 (HMGB-1)), and the incidence of multiple organ dysfunction syndrome (MODS) and mortality were observed. Results: After treatment, APACHE II score, gastrointestinal dysfunction score, and DAO, D-lactic acid, TNF-α, IL-6, and HMGB-1 levels decreased significantly in both groups, but the decrease was more significant in the treatment group than in the control group. The incidence of MODS and mortality were significantly lower in the treatment group than in the control group. Conclusion: The addition of Changweishu to routine Western treatments can improve gastrointestinal function in patients with sepsis and gastrointestinal dysfunction, as well as decreasing the incidence of MODS and mortality and improving patient prognosis.